Evolution of Char Structure and Reactivity during Gasification - Wang, Shuai (Curtin University, 2016)
The purpose of this study was to understand the effects of char structure on its gasification reactivity. FT-IR/Raman and X-ray photoelectron spectroscopies were used to obtain detailed information about the structural features of char during the gasification of mallee wood biomass in oxidising and reducing atmospheres. The effects of biomass particle size, gasification temperature and atmosphere on the evolution of char structure were investigated.